The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00330-013-2994-8
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector CT radiation dose optimisation in adults: short- and long-term effects of a clinical audit

Abstract: • External support through clinical audit may optimise default parameters of routine CT. • Reduction of 75th percentiles used as reference diagnostic levels is 18-75 %. • The effect of this audit is sustainable over time. • Dose savings through optimisation can be added to those achievable through CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…Pantos et al (18) summarized doses from 42 published studies, reporting similar doses in the head (mean effective dose, 1.9 vs 2.0 mSv) but lower doses in the chest (mean effective dose, 7.5 vs 12 mSv) and abdomen (mean effective dose, 15 vs 17 mSv). Tack et al (17) reported audit results in Luxembourg following a nationwide dose optimization effort and also found similar doses in the head (CTDI vol , 52 vs 50 mGy) and lower doses in the chest (CTDI vol , 7 vs 12 mGy) and abdomen (CTDI vol , 10 vs 12 mGy). Stamm (16) conducted a broad review of diagnostic reference levels (set at the 75th percentile) that were generally lower than our 75th percentile in distribution.…”
Section: Medical Physics: Ct Radiation Dose Data From Five Universitymentioning
confidence: 96%
See 4 more Smart Citations
“…Pantos et al (18) summarized doses from 42 published studies, reporting similar doses in the head (mean effective dose, 1.9 vs 2.0 mSv) but lower doses in the chest (mean effective dose, 7.5 vs 12 mSv) and abdomen (mean effective dose, 15 vs 17 mSv). Tack et al (17) reported audit results in Luxembourg following a nationwide dose optimization effort and also found similar doses in the head (CTDI vol , 52 vs 50 mGy) and lower doses in the chest (CTDI vol , 7 vs 12 mGy) and abdomen (CTDI vol , 10 vs 12 mGy). Stamm (16) conducted a broad review of diagnostic reference levels (set at the 75th percentile) that were generally lower than our 75th percentile in distribution.…”
Section: Medical Physics: Ct Radiation Dose Data From Five Universitymentioning
confidence: 96%
“…However, few CT diagnostic reference levels in the United States are based on large numbers of actual patient examinations; many U.S. guidelines are based on selected data submitted to demonstrate a facility's best work (10)(11)(12), and these may not reflect the routine radiation doses to which patients are exposed. In contrast, guidelines and reference levels have been created in Europe to standardize CT radiation doses (13)(14)(15)(16)(17)(18).…”
Section: Medical Physics: Ct Radiation Dose Data From Five Universitymentioning
confidence: 99%
See 3 more Smart Citations